2020
DOI: 10.3856/vol48-issue2-fulltext-2421
|View full text |Cite
|
Sign up to set email alerts
|

Chilean benthic species identified as a new source of antibiotic substances

Abstract: Benthic marine organisms are a natural source of bioactive substances with applications in medicine to treat infections, cancer and other diseases. In Chile, this community possesses rich biodiversity that has been scarcely studied as a producer of bioactive substance so far. For that reason, we studied the potential production of antibiotic substances in 28 benthic species that inhabit the coast of the Tarapacá region in northern Chile, and belong to phylum Porifera, Cnidaria, Mollusca, Sipuncula, Annelida, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…They are eaten because of their characteristic flavor, their richness of bioactive compounds (polysaccharides, fatty acids, etc. ), and their medicinal properties [17,18]. Research reports indicated that sea urchin gonads contain a high content of polyunsaturated fatty acids (PUFAs) [19], and carotenoids [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…They are eaten because of their characteristic flavor, their richness of bioactive compounds (polysaccharides, fatty acids, etc. ), and their medicinal properties [17,18]. Research reports indicated that sea urchin gonads contain a high content of polyunsaturated fatty acids (PUFAs) [19], and carotenoids [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Further, this immune system is enhanced by operating in conjunction with other strategic cellular and molecular mechanisms, such as protein synthesis against thermic shock and metallothioneins (which contain detoxicating and antioxidant properties, respectively), and in the event of extensive or persistent damage, they have the capacity for apoptosis and autophagy if a regeneration process is needed ( Chiarelli et al, 2016 ). These collective abilities have allowed these organisms to develop complex molecular elements to use in diverse biological processes; hence, as benthic organisms, they are also considered a rich source of bioactive compounds with the potential for the discovery and development of new pharmacological compounds ( Pastrana-Franco, Santafé-Patiño & Quirós-Rodríguez, 2016 ; Luparello et al, 2020 ; Strahsburger et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%